PERTIMBANGAN PEMILIHAN PENGGUNAAN MEDIA SEBAGAI SUMBER BELAJAR DALAM KEGIATAN BELAJAR MENGAJAR PENDIDIKAN AGAMA - Ni Ketut Puspita Sari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The development of science and science at this time is felt to be expanding rapidly including facilities, educational facilities and media, both electronic and non-electronic media, which are the source of learning. However, from the other side, the misuse of educational media as a learning resource has not been said to be optimally utilized to support the achievement of learning objectives in teaching and learning activities, it is necessary to consider the use of these learning media. Indeed, it cannot be denied that their use and use as a source of learning in teaching and learning activities still have many obstacles, the scarcity of education personnel who truly understand the meaning and benefits of learning resources for teaching and learning purposes is one of the factors. On the one hand, there are those who say that these learning resources are expensive, difficult to obtain and use. If it is studied and observed together that learning is everywhere around our environment. Now every subject requires media as a source of learning for students in the teaching and learning process, one of which is learning media in the learning process of Hindu religious subjects. Students who can take advantage of these learning media in the form of photos, videos or non-electronic media as well as Hindu religious educators can take advantage of electronics such as powerpoints, laptops, audio and nonelectronics such as modules or others